UENF MSV2210 and UENF MS2208: Silage and green maize hybrids for Rio de Janeiro State, Brazil - Pereira,Messias Gonzaga (2020)
Abstract This study described the main characteristics of the maize cultivars UENF MSV2210 and UENF MS2208. Adapted to the North and Northwestern regions of the state of Rio de Janeiro, they have a high agronomic performance and were developed for both silage and green maize production.